La constitution de ressources numériques en polonais — les unités simples - Hajok, Alicja (Neophilologica, 2015)
This article discusses several problems concerning the automatization of declination of simple units in Polish language. Our analysis is based on the Proteus model. The proposed solution contains a module that enables automatic generation of possible inflected variants of the given lexical units.